2012
DOI: 10.1111/j.1365-2850.2012.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

The patient's view of quality in psychiatric outpatient care

Abstract: The influence of demographic characteristics on patients' ratings of the quality of psychiatric outpatient care has been given little attention in research. The aim of the present study is to elucidate the quality of psychiatric care among outpatients and investigate demographic and clinical factors associated with the way in which this quality is perceived. A sample of 1340 outpatients from 15 general adult psychiatric clinics in Sweden completed the quality in psychiatric care-out-patient (QPC-OP), with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
6
6
0
2
Order By: Relevance
“…The present study has several strong methodological merits, such as the use of a multidimensional validated outpatient satisfaction questionnaire and a study design requiring completion of the satisfaction questionnaire at home, restraining a variant of the Hawthorne effect 3,36. The 63.8% response rate for the outpatient satisfaction questionnaire in our sample should be emphasized because it is consistent with the 65% response rate obtained using the same satisfaction questionnaire applied in French medical and surgical departments and similar to the results of the studies using other instruments in outpatient psychiatric care centers 3,31,37. This response rate emphasizes the importance that patients with substance dependence attribute to evaluating their own care, and it is a positive indicator of patients’ future willingness to measure their satisfaction in substance-dependence care settings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study has several strong methodological merits, such as the use of a multidimensional validated outpatient satisfaction questionnaire and a study design requiring completion of the satisfaction questionnaire at home, restraining a variant of the Hawthorne effect 3,36. The 63.8% response rate for the outpatient satisfaction questionnaire in our sample should be emphasized because it is consistent with the 65% response rate obtained using the same satisfaction questionnaire applied in French medical and surgical departments and similar to the results of the studies using other instruments in outpatient psychiatric care centers 3,31,37. This response rate emphasizes the importance that patients with substance dependence attribute to evaluating their own care, and it is a positive indicator of patients’ future willingness to measure their satisfaction in substance-dependence care settings.…”
Section: Discussionsupporting
confidence: 81%
“…The results showed that the mean satisfaction scores in domains “consultation with the doctor”, “appointment making” and “reception” were well below 80, whereas the mean score for the “waiting time” dimension was more aligned with the previous results 3. Long waiting time has been identified in psychiatric outpatient settings as a primary cause of low patient satisfaction ratings, and previous studies have reported that patients who had waited for a long time were more dissatisfied with staff, with their prospects of influencing their care, and with the care that they received 31,32. In light of these findings, the results of this study indicated that practitioners working in outpatient settings must continually improve the technical and interpersonal aspects of the care that they provide because dissatisfaction with initial contact might lead patients to cease care or consult elsewhere 19…”
Section: Discussionsupporting
confidence: 69%
“…One possible explanation is that younger staff make greater demands on quality of care, based on results showing that younger people in general are less satisfied with the quality of care than older people [48]. This is in line with previous studies on psychiatric patients showing that older patients have higher quality of care ratings than younger patients [21,23,49]. Whether this finding is related to a general age/generation difference or is specific to psychiatry staff needs to be examined in future research.…”
Section: Discussionsupporting
confidence: 62%
“…However, this proportion is lower than that found among general psychiatric in-patients and out-patients in Sweden (Lundqvist, Ahlström, Wilde-Larsson, & Schröder, 2012;Schröder et al, 2010Schröder et al, , 2011. However, this proportion is lower than that found among general psychiatric in-patients and out-patients in Sweden (Lundqvist, Ahlström, Wilde-Larsson, & Schröder, 2012;Schröder et al, 2010Schröder et al, , 2011.…”
Section: ▪ Discussionmentioning
confidence: 54%